Qur’ani Paradigm in Professional Development of Mathematics Teacher - Fathani, Abdul Halim (Lembaran Ilmu Kependidikan, 2023)
This study aims to find out how the concept and form of professionalism of Mathematics teachers in mathematics learning by studying the content of the Qur'an. The context of mathematics teachers in this article is an important highlight because Mathematics is a universal science that can be used as an axis in the process of taqarrub ilallah and as a means of worshiping Allah SWT. The method used in this research was literature review by reviewing and collecting data sources that became research references. There were two sources of data used in this study, namely primary data sources and secondary data sources. The verses of the Qur'an studied were primary data sources which were then supported by secondary data sources in the form of scientific articles and other written works. As a source of knowledge and guidance for humans, it includes also being a guide for Mathematics teachers to know how to best transfer knowledge and improve their professionalism. The results of the analysis of the data obtained in this study are in the form of the implied message of the Qur'an to a teacher who is obliged to convey his knowledge to those who have the right to receive it (students) by having words, actions, and a gentle heart, always showing a truth, and put forward deliberation with students and fellow teachers in determining the direction of learning